Effects of basalt fiber and polyvinyl alcohol fiber on the properties of recycled aggregate concrete and optimization of fiber contents. (18th July 2022) - Du, Xiaoqi; Li, Yanlong; Si, Zheng; Huang, Lingzhi; Chen, Xuguang
Highlights: Hybrid BF and PVAF exhibited an excellent coupling role in improving the mechanical properties and durability of RAC. The optimal fiber content of RAC was determined based on the tests and response surface optimization. The optimum fiber contents of BF and PVAF were 0.274% and 0.102%, respectively. Abstract: With the rapid economic development, a great quantity of concrete structures is facing dismantling and rebuilding. In this process, many recycled aggregates (RA) that will have an adverse effect on the environment will be produced. Fiber-reinforced RA concrete (RAC) (FRRAC) was prepared using single-incorporated basalt fiber (BF), single-incorporated polyvinyl alcohol fiber (PVAF), and double-incorporated BF with PVAF as micro-reinforced materials to improve the environment and the performance of RAC. The influence of fibers on the performance of RAC was analyzed on the basis of workability, mechanical properties and durability along with the desire function to achieve the multi-objective optimization of the comprehensive performance of FRRAC to obtain the optimal content of hybrid fibers. Results showed that the incorporation of fiber improved the mechanical performance and durability of RAC. The double-incorporated BF with PVAF could play an excellent coupling role, that is, BF and PVAF mainly improved the strength and toughness of RAC, respectively. The optimum contents of BF and PVAF for preparing unit volume FRRAC were 0.274% and 0.102%, respectively. This ratio could prepare FRRAC with compressive strength of 54.3 MPa, splitting tensile strength of 3.29 MPa, flexural strength of 3.67 MPa, compressive strength of 49.9 MPa after 200 freeze–thaw cycles and compressive strength of 50.7 MPa after 120 sulfate wetting–drying cycles.